2005
DOI: 10.1063/1.2123369
|View full text |Cite|
|
Sign up to set email alerts
|

Elasticity of planar fiber networks

Abstract: A micromechanics model is proposed for the elasticity of planar fiber networks ͑FNs͒. The FN is created by random deposition of linearly elastic straight rods within a region. The rods are bonded rigidly at contacts. Under external in-plane loading, the FN deformation consists of fiber bending, elongation, and contraction. An effective constitutive relation for fiber network is developed by averaging the strain energy dissipated by all possible fiber deformations in all directions. Numerical calculations are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(49 citation statements)
references
References 43 publications
1
48
0
Order By: Relevance
“…It was found that the stable jet exists in the radius range less than a critical value defined by the dielectric properties and surface tension of the fluid. The process of jet initiation was analyzed as an electrical 14 break-up of a charged meniscus. The surface shape was defined by the balance of the hydrostatic pressure, surface tension, and electric forces resulting from interactions of the electric field with free charges and dielectric polarization of the fluid.…”
Section: Nanomanufacturing Of High-performance Nanofibers For Next Gementioning
confidence: 99%
“…It was found that the stable jet exists in the radius range less than a critical value defined by the dielectric properties and surface tension of the fluid. The process of jet initiation was analyzed as an electrical 14 break-up of a charged meniscus. The surface shape was defined by the balance of the hydrostatic pressure, surface tension, and electric forces resulting from interactions of the electric field with free charges and dielectric polarization of the fluid.…”
Section: Nanomanufacturing Of High-performance Nanofibers For Next Gementioning
confidence: 99%
“…The stiffness is given as a function of only a few parameters: the degree of bonding, the dimensions of the fibres, the elastic constants of the fibre material and the density of fibres. A very similar micromechanics model is given in [16] for the elasticity of planar fibre networks made from short fibres. The rods are still bonded rigidly at contacts in [16] and under external in-plane loading.…”
mentioning
confidence: 99%
“…Computation time is therefore one of the primary concerns associated with meso-scale FEA models for DFC materials. 2D models are the most computationally inexpensive option, using 1D linear beam elements to represent fibre bundles randomly distributed in 2D space [7,[22][23][24][25][26]. However, this approach overlooks fibre crimping and allows bundle-bundle penetration, as all bundles are deposited on the same plane, reducing accuracy.…”
Section: Introductionmentioning
confidence: 99%